2021
DOI: 10.1152/ajpregu.00115.2020
|View full text |Cite
|
Sign up to set email alerts
|

l-Citrulline supplementation during pregnancy improves perinatal and postpartum maternal vascular function in a mouse model of preeclampsia

Abstract: Preeclampsia is a spontaneously occurring pregnancy complication diagnosed by new onset hypertension and end-organ dysfunction with or without proteinuria. This pregnancy-specific syndrome contributes to maternal morbidity and mortality and can have detrimental effects on fetal outcome. Preeclampsia is also linked to increased risk of maternal cardiovascular disease throughout life. Despite intense investigation of this disorder, few treatment options are available. The aim of this study was to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The reduced Cit concentration may indicate that Cit is being utilized for placental and fetal development, which can be beneficial for vascular health. 45,46 Our correlation analysis showed a significant positive relationship between placental vascular density and cord blood amino acid concentration (Fig. S1).…”
Section: Discussionmentioning
confidence: 76%
“…The reduced Cit concentration may indicate that Cit is being utilized for placental and fetal development, which can be beneficial for vascular health. 45,46 Our correlation analysis showed a significant positive relationship between placental vascular density and cord blood amino acid concentration (Fig. S1).…”
Section: Discussionmentioning
confidence: 76%
“…However, most of them studied the correlation between serum levels of citrulline and preeclampsia, and none of them studied the direct effect of citrulline supplementation in preeclampsia. Only shortly after we had completed this study, a report was published online ahead of print, which demonstrated that citrulline improves perinatal and postpartum maternal vascular function in a preeclampsia‐like genetically modified mouse model (Gemmel et al, 2021). Compatible with our findings, Gemmel et al suggest that citrulline has beneficial effects on maternal vascular health in C1q −/− mice, attributable to NO signalling.…”
Section: Discussionmentioning
confidence: 99%
“…In the male C57BL/6J×female C57BL/6J C1q − / − rodent model of preeclampsia, L-citrulline supplementation during pregnancy was shown to improve maternal NO-mediated vascular function at 7 months postpartum via conversion to L-arginine. 36 Booz et al 37 verified that inhibition of AT1-AAs improves the changes in blood pressure, cardiac hypertrophy, and cardiac mitochondrial function in the reduced uterine perfusion pressure rat model of preeclampsia, not only during pregnancy but also at 10 weeks postpartum. Actually, there has been a long history of using angiotensin receptor blockers to selectively block AT1R and treat CVD, similar to treatments for hypertension.…”
Section: Cardiovascular Consequences For Women Diagnosed With Preecla...mentioning
confidence: 96%